1997
DOI: 10.1096/fasebj.11.12.9337151
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of diadenosine polyphosphate transport into chromaffin granules from adrenal medulla

Abstract: The transport of diadenosine polyphosphates into chromaffin granules from bovine adrenal medulla has been studied by using the radiolabeled substrate [3H]Ap5A and the fluorescent substrate analog di(1,N6-ethenoadenosine)polyphosphate, epsilon-(Ap(n)A) (n=3-5). The vesicular concentration increase was time dependent and the substrates were not metabolized to any extent during the transport experiments. The saturation curve indicates the existence of kinetic and allosteric cooperativity during Ap(n)A (diadenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 1 publication
(1 reference statement)
1
19
0
Order By: Relevance
“…ATP transport is driven by Δψ but not by ΔpH and is stimulated in the presence of millimolar order Cl − and partially inhibited by atractyloside [27]. The uptake of fluorescent ATP analogues and diadenosine polyphosphate ( 3 HAp5A) by chromaffin granule ghosts and synaptic vesicles, respectively, has also been reported [28][29][30].…”
Section: Vesicular Storage Of Atpmentioning
confidence: 99%
“…ATP transport is driven by Δψ but not by ΔpH and is stimulated in the presence of millimolar order Cl − and partially inhibited by atractyloside [27]. The uptake of fluorescent ATP analogues and diadenosine polyphosphate ( 3 HAp5A) by chromaffin granule ghosts and synaptic vesicles, respectively, has also been reported [28][29][30].…”
Section: Vesicular Storage Of Atpmentioning
confidence: 99%
“…In 1997, by means of a combination of radiometric and etheno-derivative-based fluorimetric techniques, we described for the first time the transport of diadenosine polyphosphates into secretory granules, the chromaffin granules [Gualix et al, 1997].…”
Section: Diadenosine Polyphosphate Transport Into Chromaffin Granulesmentioning
confidence: 99%
“…The transport of diadenosine polyphosphates into secretory vesicles regulates the accessibility of these compounds to the extracellular space but also could be a mechanism for finishing their cytosolic actions, which would give this transport process a relevant physiological meaning. On the other hand, diadenosine pentaphosphate (Ap 5 A) transport into chromaffin granules could be inhibited by other diadenosine polyphosphates (Ap 3 A and Ap 4 A) and, to the same extent, by the non-hydrolizable analogs of ATP and ADP, ATPγS and ADPβS (Gualix et al, 1997). The inhibitory pattern of nucleotide analogs on Ap n A transport suggested that both types of substances, adenine mono-and dinucleotide, share a common vesicular transporter.…”
Section: Diadenosine Polyphosphate Transport Into Chromaffin Granulesmentioning
confidence: 99%
“…Vesicular uptake of these compounds is mediated through a transporter that shows a broad range of specificity, being able to internalize a large variety of mononucleotides (such ATP ADP, AMP, UTP, etc.) as well as the diadenosine polyphosphates [5,6]. All these secretory systems respond to depolarizing agents or secretagogues by releasing their vesicular content to the Electronic supplementary material The online version of this article (doi:10.1007/s11302-013-9382-3) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…extracellular medium [4,7]. In this regard, push-pull cannula experiments performed in living rats showed that after amphetamine stimulation, rat neostriatum releases diadenosine tetraphosphate, Ap 4 A, and diadenosine pentaphosphate, Ap 5 A, which can be detected in the perfusion samples at concentrations in the nanomolar range [8].…”
Section: Introductionmentioning
confidence: 99%